2021
DOI: 10.1371/journal.pone.0247000
|View full text |Cite
|
Sign up to set email alerts
|

Viral causes of severe acute respiratory infection in hospitalized children and association with outcomes: A two-year prospective surveillance study in Suriname

Abstract: Background Viruses are the most frequent cause of severe acute respiratory infection (SARI) in children. It is currently unknown whether presence of a virus, the number of viruses, or type of virus, are associated with clinical outcomes of pediatric SARI in developing countries. Methods Between 2012 and 2014 nasopharyngeal swabs and demographic and clinical variables were prospectively collected for surveillance of viral causes of SARI in Surinamese children within 48 hours after hospitalization. These swabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
6
14
0
Order By: Relevance
“…Nevertheless, ADV and CoV were only detected in 4.1% and 3.7% of cases, respectively. ese results are comparable to those reported by several studies [19,24]. It was noticeable that HRV was the most detected respiratory pathogen in studies conducted in our country and other ones [1,4,9,18,19,20,24,29].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, ADV and CoV were only detected in 4.1% and 3.7% of cases, respectively. ese results are comparable to those reported by several studies [19,24]. It was noticeable that HRV was the most detected respiratory pathogen in studies conducted in our country and other ones [1,4,9,18,19,20,24,29].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, male dominance in children with SARI was found (58.1%), confirming the results of previous studies [4,19,23,24]. According to McClelland and Smith [25], this dominance can be explained by an interaction between gender-specific immune responses and immune responses to specific microbes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nasopharyngeal swabs sample handling and analysis were done as described before. 19 In short, extraction of genetic material was performed with the QIAamp MinElute Virus Spin Kit (Qiagen) and detection of viruses was performed with the Respifinder SMART 22 multiplex PCR kit (Pathofinder BV) on a Lightcycler 480 (Hoffmann La Roche), according to the manufacturers' instructions. Blood samples were collected in serum microtainers using venipuncture, capillary collection, or blood collection during the insertion of a venous cannula.…”
Section: Sample Collection and Analysismentioning
confidence: 99%